ANALISIS KETIMPANGAN PENDAPATAN DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2015-2020 (Studi Kasus di 4 Kabupaten dan 1 Kota di Provinsi DIY) - Muharam, Kautsar Ibnu (Journal of Development Economic and Social Studies, 2022)
The purpose of this research is to analyze the effects economic growth, education, population, and poverty on income disparity in Yogyakarta province using Gini index. Common Effect Model (CEM) was used to analyze the panel data of five regions in the province from 2015 to 2020. This study finds that economic growth and population have negative but insignificant effects on income disparity, that education and poverty positively and significantly influence the disparity, and that education has the most dominant effect of all. Therefore, this research recommends the birth of policies that address economic growth, education, population, and poverty issues such as building public facilities and investing more in education especially in lagged regencies. The government also need to organize trainings and workshop about entrepreneurship to the public, especially the unemployed ones, so that they can open their own business and work according to their capabilities.